On the hierarchical inheritance of aftereffects in the visual system - Dickinson, James E.; Badcock, David R. (Frontiers in Psychology, 2013)
The emotion perceived in a face can be influenced by prior exposure to a face expressing a different emotion. Here we show that displacement along a particular emotional axis, that encoding happiness and sadness, can be effected solely by a systematic change in the angle, at the center of the mouth, between the left and right halves of the mouth. We then demonstrate that adaptation to a face with the mouth distorted to change this angle, such that the face expresses an emotion on this axis, causes a face with a neutral expression to be perceived as having the opposite expression. By abstracting the mouths from the faces and examining the magnitude of the angle aftereffects in the mouths alone and in an unfamiliar orientation, we show that the magnitudes of the angle aftereffects are sufficient to account for the changes in perceived emotion in the faces. Further, by applying the distortion to the mouths asymmetrically so that the distortion is manifested by a change in orientation of the mouth stimulus rather than a change in angle, we show that the magnitude of the aftereffect can be predicted by the local tilt aftereffect. We argue, therefore, that the aftereffects of emotion are due to misperception of morphology of the face and that the misperception is due to the local change in perceived orientation due to the systematic application of the tilt aftereffect in a tilt aftereffect field. All adaptation experiments were performed using stimuli that were either high-pass or low-pass filtered for spatial frequency. Results showed that the spatial frequency specificity of the aftereffects was the same for the face, angled mouth, and oriented mouth stimuli, lending further support to the hypothesis that the aftereffects are instantiated in processes early in the visual cortex and that the aftereffects assumed to be higher level are, in fact, inherited.